Education and Effectiveness of Parent Participation in The Provision of Blood Supplementation Tablets on Increasing Hemoglobin Levels in Adolescent Girls - Theresia Limbong; Syaniah Umar; Suriana Koro (Humanistic Network for Science and Technology (HNST), 2022)
Iron anemia control is a program to prevent anemia through health education by giving blood supplement tablets to adolescent girls. This study aims to study the effect of education and the effectiveness of parental participation in giving blood-added tablets to increase blood hemoglobin levels. The study was carried out at SMA PGRI Makassar from January to October 2021. The population was adolescent girls aged 12-18 years who participate in the blood-boosting tablet supplement program with a total of 45 respondents. The sample size was determined by the Slovin formula so that 41 were obtained which were taken using a simple random sampling technique. Data were collected using a questionnaire before and after being given an anemia education model and parental participation in increasing hemoglobin levels. To determine the hemoglobin level used Sahli's Hb with units of g/dl. In the paired t-test analysis, there was a significant change in the knowledge of adolescent girls about anemia after being given the education model with p-value = 0.000 (less than 0.05). There was a significant difference in parental participation in the administration of blood-added tablet supplements. As conclusion, education and the effectiveness of parental participation affect increasing hemoglobin levels. Keywords: adolescent girls; parental participation; blood supplement tablet (TTD); Hb level